EFEKTIVITAS PEMBELAJARAN DARING BERBANTUAN YOUTUBE DENGAN MODEL PEER TEACHING TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA - Anisa Wijayanti (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2021)
The COVID-19 pandemic has forced learning to be done online using certain media and applications. This study was aimed to analyze the effectiveness of Peer Teaching Model assisted by Youtube app on student achievement in mathematics learning from home process during pandemic COVID-19 in term of cognitive, affective and student participation. This research is deskriptif study with a mixed-method approach. The subject in this study were students in grade 11.1 and 11.2 MIPA at a state senior high school in Bogor in the 2nd semester of 2020/2021 academic year. Data collection techniques were carried out through tests to determine student achievement, questionnaires to measure student interest in the learning model and the media used, as well as assignments and interviews to determine student participation. The effectiveness criterion used is that at least 75% of students have a positive response and have a test score above Kriteria Ketuntasan Minimal (KKM). The results showed that the percentage of student learning completeness was 77% (good category), the positive response of students was 80.29% and participation in assignments was very good.